Employer branding and employee performance at KAI: employee retention' role as mediator - Srimulyani, Veronika Agustini; Hermanto, Yustinus Budi (Faculty of Communications Science, Dr. Soetomo University, 2022)
Today's job seekers prefer well-known companies, even though they're less likely to be accepted. The HR team must brand the company as an employer. Employer branding can be a company's image, values, and work culture. Employer branding has a greater impact on employee loyalty than non-emotional factors on employees. This study aims to explain 1) employer branding's impact on employee retention and performance, 2) employee retention's impact on employee performance, and 3) employer branding's impact on employee performance through employee retention as a mediator. 110 frontline workers from PT Kereta Api Indonesia (Persero) DAOP VII Madiun made up the research sample. The sampling was proportional random. Using SPSS and Sobel, this study uses descriptive and inferential analysis. Influence test results show that employer branding increases employee retention and performance, and employee retention increases employee performance. The results of path analysis and Sobel test of the mediator's role show that the direct effect of employer branding on employee retention after being controlled by employee retention as a mediator is not significant. Employee retention acts as a full mediator for employer branding's effect on employee performance, according to the mediator test. 2) Companies can improve employee performance by improving employee retention via career opportunities, awards, and employee relationships.